The Silage Quality of Pennisetum purpureum Cultivar Gamma Umami Mixed with Calliandra calothyrsus and Lactiplantibacillus plantarum - Mudhita, I. K.; Putra, R. A.; Rahman, M. M.; Widyobroto, B. P.; Agussalim; Umami, N. (Tropical Animal Science Journal, 2024)
This study aimed to determine the effect of Calliandra calothyrsus supplementation and inoculation of Lactiplantibacillus plantarum (L. plantarum) on Penisetum purpureum cv. Gamma Umami grass fermentative and chemical quality and nutrient degradability. The study used a completely randomized design with 3 × 3 factorial patterns. The first factor was Calliandra supplementation levels at 10%, 20%, and 30%; the second was L. plantarum inoculation levels at 0%, 2%, and 4%. The variables measured included chemical fermentation profiles, chemical composition, and rumen fermentation and degradability parameters. The result showed that a higher level of C. calothyrsus supplementation concomitant increased silage pH and NH3-N concentration (p